Risk perception and tolerance shape variation in agricultural use for a transboundary elephant population. Issue 1 (2nd November 2021) - Hahn, Nathan R.; Wall, Jake; Denninger‐Snyder, Kristen; Goss, Marc; Sairowua, Wilson; Mbise, Noel; Estes, Anna Bond; Ndambuki, Stephen; Mjingo, Eblate Ernest; Douglas‐Hamiliton, Iain; Wittemyer, George
Abstract: To conserve wide‐ranging species in human‐modified landscapes, it is essential to understand how animals selectively use or avoid cultivated areas. Use of agriculture leads to human–wildlife conflict, but evidence suggests that individuals may differ in their tendency to be involved in conflict. This is particularly relevant to wild elephant populations. We analysed GPS data of 66 free‐ranging elephants in the Serengeti‐Mara ecosystem to quantify their use of agriculture. We then examined factors influencing the level of agricultural use, individual change in use across years and differences in activity budgets associated with use. Using clustering methods, our data grouped into four agricultural use tactics: rare (<0.6% time in agriculture; 26% of population), sporadic (0.6%–3.8%; 34%), seasonal (3.9%–12.8%; 31%) and habitual (>12.8%; 9%). Sporadic and seasonal individuals represented two‐thirds (67%) of recorded GPS fixes in agriculture, compared to 32% from habitual individuals. Increased agricultural use was associated with higher daily distance travelled and larger home range size, but not with age or sex. Individual tactic change was prevalent and the habitual tactic was maintained in consecutive years by only five elephants. Across tactics, individuals switched from diurnal to nocturnal activity during agricultural use, interpreted as representing similar risk perception of cultivated areas. Conversely, tactic choice appeared to be associated with differences in risk tolerance between individuals. Together, our results suggest that elephants are balancing the costs and benefits of crop usage at both fine (e.g. crop raid events) and long (e.g. yearly tactic change) temporal scales. The high proportion of sporadic and seasonal tactics also highlights the importance of mitigation strategies that address conflict arising from many animals, rather than targeted management of habitual crop raiders. Our approach can be applied to other species and systems to characterize individual variation in human resource use and inform mitigations for human–wildlife coexistence. Abstract : To conserve wide‐ranging species in human‐modified landscapes, it is essential to understand how animals selectively use or avoid cultivated areas. In elephants and other conflict‐prone species, it is thought that a few individuals in the population cause the majority of conflict. The study analysed GPS data of 66 free‐ranging elephants over 9 years to quantify the extent of crop use and investigate drivers of variation in use between elephants. The results showed that 80% of the population used agriculture at least sporadically, indicating that more individuals are at risk of conflict than previously thought. Further, patterns of conflict were complex in that individuals frequently changed their agricultural use between years. In contrast to hazing or removal of problem animals, mitigations for large numbers of elephants, such as chili and beehive fencing and buffer crops, should be more effective in reducing conflict. This study highlights the complexity of conflict behaviour and provides a framework to assess other populations and species prone to conflict with humans.